The Influence of Oral Bacteria on Epithelial Cell Migration In Vitro - Alexa M. G. A. Laheij; Johannes J. de Soet; Enno C. I. Veerman; Jan G. M. Bolscher; Cor van Loveren (Mediators of Inflammation)
Oral ulcerations often arise as a side effect from chemo- and radiation therapy. In a previous clinical study, Porphyromonas gingivalis was identified as a positive predictor for oral ulcerations after hematopoetic stem cell transplantation, possibly incriminating P. gingivalis in delayed healing of the ulcerations. Therefore, it was tested whether P. gingivalis and its secreted products could inhibit the migration of oral epithelial cells in an in vitro scratch assay. To compare, the oral bacteria Prevotella nigrescens, Prevotella intermedia, Tannerella forsythia, and Streptococcus mitis were included. A standardized scratch was made in a confluent layer of human oral epithelial cells. The epithelial cells were challenged with bacterial cells and with medium containing secretions of these bacteria. Closure of the scratch was measured after 17 h using a phase contrast microscope. P. gingivalis, P. nigrescens, and secretions of P. gingivalis strongly inhibited cell migration. A challenge with 1000 heat-killed bacteria versus 1 epithelial cell resulted in a relative closure of the scratch of 25% for P. gingivalis and 20% for P. nigrescens. Weaker inhibitory effects were found for the other bacteria. The results confirmed our hypothesis that the oral bacteria may be involved in delayed wound healing.